(untitled) (Nigerian Journal of Technology, 2020)
This study assessed the effect of partial replacement of cement with plantain peel ash (PPA) and Polystrene (POL) on the compressive strength of concrete as a means of managing waste. Concrete specimens were prepared with a mix ratio of 1:2:4 (cement: sand: granite) water/cement ratio of 0.6, thereafter cement was partially replaced with PPA, POL and PPA/POL in increasing percentages of 5, 10, 15 and 20% by weight. Physical, chemical and microstructural analyses were also conducted on the aggregates and materials used. Workability of the concrete specimens was observed to improve upon addition of PPA and POL separately but not with blended PPA/POL while compressive strength decreased with addition of the three compounds. The observed results can be attributed to the lack of sufficient cementitious properties in the materials, and hence, the study discourages the use of these materials as they do not significantly improve concrete strength. http://dx.doi.org/10.4314/njt.v39i3.7